Developing a tool to assess women’s knowledge and attitude toward managing prediabetes: 10.55131/jphd/2025/230103 - Nuryani, Nuryani; Khomsan, Ali; Dewi, Mira; Dwiriani, Cesilia Meti; Lukito, Widjaja (Journal of Public Health and Development, 2024)
Prediabetes is a state caused by insulin resistance, resulting in higher blood glucose levels. The incidence of diabetes mellitus can increase when this condition is not adequately treated. Therefore, this study aimed to develop questionnaire that can assess knowledge and attitude toward prediabetes management. The descriptive study that includes validity and reliability tests. The content validity test used 10 panelists of public health nutritionists and nutrition education experts. Meanwhile, face validity used 10 participants, and reliability test included 30 adult women participants. Content validity index (CVI) and kappa statistics score were also adopted in this study. Face validity was carried out by calculating the impact score while reliability test used Cronbach’s alpha. The content validity of knowledge component questionnaire was analyzed separately for the clarity (CVI = 0.44 – 0.88) and relevance aspect (CVI = 0.77 – 1). The result of the kappa statistic showed 10 items questions in the low category, and each 5 items had a sufficient and very good rating. The face validity assessment with impact score analysis, ranged from 3.0 – 4.6. The analysis of correlation (p-value < 0.05) was carried out on 7 questions items. Reliability test using using Cronbach’s alpha showed a coefficient of 0.642. Furthermore, content validity analysis of attitude component questionnaire was performed separately for clarity (CVI = 0.727 – 1) and relevance aspect (CVI = 0.909 – 1). The result of the kappa statistic showed 2 items statement in low and 18 in very good category. Face validity with impact score analysis ranged from 2.5 - 3.1, and the correlation analysis (p-value < 0.05) on the 6-items statement had a Cronbach’s alpha of 0.772. The study conclusion that knowledge and attitude questionnaire prediabetes management had good validity and reliability in adult women group.